2011
DOI: 10.1007/s00534-011-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of oral S‐1 with concurrent radiotherapy followed by chemotherapy with S‐1 alone for locally advanced pancreatic cancer

Abstract: Combination therapy with S-1 and radiation in patients with locally advanced and unresectable pancreatic cancer is considered a promising, well-tolerated regimen that can be recommended as an effective treatment for locally advanced pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The MST of BR-PDAC patients with an NLR of >3 (n = 12) or a PLR of >225 (n = 8) was 10.2 months in each group. In recent phase II studies, the MST of patients with locally advanced UR-PDAC who received non-surgical treatment has been reported to be 13-17 months [32][33][34][35]. It is obviously not beneficial for these patients to undergo an "upfront" surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The MST of BR-PDAC patients with an NLR of >3 (n = 12) or a PLR of >225 (n = 8) was 10.2 months in each group. In recent phase II studies, the MST of patients with locally advanced UR-PDAC who received non-surgical treatment has been reported to be 13-17 months [32][33][34][35]. It is obviously not beneficial for these patients to undergo an "upfront" surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of the patients with locally advanced pancreatic cancers that received chemoradiotherapy or radiotherapy alone or chemotherapy alone was found to be between 5.7-16.8 in a previous randomized controlled study [8][9][10][12][13][14][15][16]. In particular, the results of the median survival time with chemoradiotherapy with TS-1 had been 11-16.8 months [17][18][19][20][21][22]. Our study included 12 patients with TS-1 and a median survival time of 10.8 months, which is slightly inferior compared to previous reports.…”
Section: Discussionmentioning
confidence: 90%
“…S-1 is an oral 5-FU prodrug. Several phase II studies of S-1 cCRT have demonstrated an acceptable toxicity profile and promising efficacy with a response rate of 24%-41% and median survival of 12.9-16.8 mouths (21)(22)(23)(24). Nowadays, it's widely used in Asia.…”
Section: Discussionmentioning
confidence: 99%